NATURAL IONIZING IRRADIATION SOURCES IN TYVA REPUBLIC - S. A. Daktaalai (Радиационная гигиена)
Average annual individual effective doses from natural exposure of the population of Russian Federation are very diverse. At the same time exposure doses inside one territory could also be very different from the average value for this territory. In this paper we evaluated doses of natural exposure of the population living in different administrative units of the Tyva Republic. For the calculation of natural exposure dose we used the results of studies conducted in various administrative areas of the Tyva Republic in the period from 2007 to 2011. It is shown that the range of the average annual individual effective doses of natural exposure of the population in various administrative areas of the Tyva Republic is very broad. Thus, in some administrative areas of the republic average annual individual effective dose of natural exposure differs from the average regional value – 5,21 mSv/year in two or more times. The author also points out the main reasons for the enhanced natural exposure of the population of Tyva Republic, carries out the dependence of gamma background in the open places in the administrative areas on their geographical location in the region.